THE ANALYSIS OF ENGLISH LECTURERS’ CLASSROOM-BASED READING ASSESSMENTS TO IMPROVE STUDENTS’ READING COMPREHENSION - Yanuarti Apsari; Acep Haryudin (Eltin Journal : Journal of English Language Teaching in Indonesia, 2017)
The objectives of this research are to identify techniques that the lecturers use in assessing readingcomprehension and to find the way English lecturers construct classroom-based reading assessments.Three English lecturers were selected as the respondents of this research. The data were obtainedthrough classroom observation and interview. Then, they were analyzed and reported descriptively.The results of this research revealed that in assessing reading comprehension all respondents usedvarious techniques such as short answer question, matching test, multiple choice and observation(teacher made method) and summary and retelling (students conducted method). In addition, they usedthe different sources in designing assessment instruments. The sources were taken not only fromtextbook but also from internet, journals and other textbooks. Keywords: English lecturers, Classroom-Based Reading Assessments, Reading Comprehension